2021
DOI: 10.1111/tgis.12852
|View full text |Cite
|
Sign up to set email alerts
|

Slope, aspect, and hillshade algorithms for non‐square digital elevation models

Abstract: Focal operations operate on raster cells and their neighbors, and provide some of the most useful displays for digital elevation models (DEMs), including slope, aspect, and hillshade displays. Computation of these parameters requires data spacing, and many GIS programs have required that the spacing be the same in both directions of the grid. At the same time, the mapping agencies supplying DEMs produce most of the moderate-scale

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…At best, this is suboptimal since projection alters properties of the data (Guth & Kane, 2021) and is not possible at a global extent. The algorithms used for planar data cannot be applied to unprojected data due to inherently different geometries of the surface (planar vs spheroid); however, algorithms do exist to measure slope, aspect, and curvature for unprojected data (Florinsky, 2017; Guth & Kane, 2021) via the use of geodetic formulas (Karney, 2013; Vincenty, 1975). These may be implemented in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At best, this is suboptimal since projection alters properties of the data (Guth & Kane, 2021) and is not possible at a global extent. The algorithms used for planar data cannot be applied to unprojected data due to inherently different geometries of the surface (planar vs spheroid); however, algorithms do exist to measure slope, aspect, and curvature for unprojected data (Florinsky, 2017; Guth & Kane, 2021) via the use of geodetic formulas (Karney, 2013; Vincenty, 1975). These may be implemented in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This prevents calculation of slope, aspect, curvature, and some forms of roughness for unprojected data, and, therefore, requires DTMs to be reprojected prior to conducting certain calculations. At best, this is suboptimal since projection alters properties of the data (Guth & Kane, 2021) and is not possible at a global extent. The algorithms used for planar data cannot be applied to unprojected data due to inherently different geometries of the surface (planar vs spheroid); however, algorithms do exist to measure slope, aspect, and curvature for unprojected data (Florinsky, 2017; Guth & Kane, 2021) via the use of geodetic formulas (Karney, 2013; Vincenty, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…6. All computations were performed in native geographic coordinates (Guth and Kane, 2021). While there are differences in the statistics between the rectangular 1" pixels and square 30 m pixels, interpolating to UTM coordinates adds its own changes to computations done on the DEM which we avoided.…”
Section: Comparing the Demix Wine Contest Methods And Rankings To Pre...mentioning
confidence: 99%
“…Aggregation -global DEMs are provided in geographic coordinates whereas reference DEMs tipically use local projections such as UTM to avoid spatial distortions. While interpolation has been used to solve the reprojection issues, (Guth and Kane, 2021) showed that re-interpolation changed the characteristics of the DEM and that care in the algorithms allows accurate computations with the geographic coordinates without introducing significant interpolation errors. The UTM or comparable coordinates of each pixel in the source reference DEMs are converted to latitude and longitude in the WGS84 system, and mapped to the corresponding pixel in the test DEM.…”
Section: Preparation Of the Reference Demsmentioning
confidence: 99%
“…Por ejemplo, para la pendiente podríamos considerar su cálculo usando cuatro vecinos (Fleming y Hoffer 1979), ocho vecinos (Horn 1981), ocho vecinos ponderado por la distancia o con igual peso (Sharpnack y Akin 1969), por medio de cuatro triángulos (Mathur 1989). Guth (1995) y Hodgson (1998) presentan una comparación de algunas de estas opciones. Otro caso similar en cuanto a las numerosas opciones existentes, que se relaciona directamente con la determinación de cuencas y redes, es el procesado de depresiones o pozos; aquí podemos citar, entre otras, las propuestas de Jenson and Domingue (1988), Hutchinson (1989), Martz and Garbrecht (1998) y Planchon and Darboux (2002).…”
Section: La Información Se Procesa Y Esto Afecta a Su Calidadunclassified